БИОНИЧЕСКИЙ ПАРАМЕТРИЧЕСКИЙ ПАРЕТО-ОПТИМАЛЬНЫЙ СИНТЕЗ АКСИАЛЬНО-СИММЕТРИЧНЫХ ИСТОЧНИКОВ МАГНИТНЫХ ПОЛЕЙ С ФЕРРОМАГНИТНЫМИ ЭЛЕМЕНТАМИ КОНСТРУКЦИИ - Гальченко, В.Я.; Якимов, А.Н.; Остапущенко, Д.Л. (Інститут електродинаміки НАН України, Київ, 2012)
In this research a method of efficient parametric synthesis of axially symmetric magnetic field sources with ferromagnetic elements has been developed that allows finding a solution of optimization problem in multicriterion statement. Problem of magnetic field analysis is solved with taking into account linear and nonlinear properties of ferromagnetic with using of border and volume integral equations approach. Developed by authors a hybrid optimization algorithm by swarm of particles with evolutionary formation of swarm composition is used to provide a seeking of global solution of the problem. This algorithm has high convergence speed, and it is economical in terms of an objective function computations. References 6.